Survey on the Current Status of Elderly Health Services in 1,305 Medical Institutions in Guangxi - Huang D; Zhou C; Li C; Huang H; Pan X; Pan Y; Pan Q; Lai L (Dove Medical Press, 2024)
Dongmei Huang,1 Caizhong Zhou,2 Caili Li,3 Huiqiao Huang,4 Xiao Pan,3 Yanfei Pan,3 Qini Pan,3 Lichong Lai3 1Department of Rehabilitation Medicine, The Second Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People's Republic of China; 2Department of Internal Medicine, Second People's Hospital of Teng County, Wuzhou, Guangxi, People's Republic of China; 3Nursing Department, The Second Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People's Republic of China; 4Party Committee Office, The Second Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People's Republic of ChinaCorrespondence: Huiqiao Huang, Email hhq@sr.gxmu.edu.cnObjective: To investigate the current status of elderly health services in medical institutions at all levels within Guangxi Province, China.Methods: Using a purposeful sampling method, a questionnaire survey was conducted from July 24, 2023 to October 24, 2023 on the general situation, human resources, rehabilitation medicine, nursing services, and the development of hospice care at 1305 medical institutions in Guangxi.Results: Among the surveyed 1305 medical institutions in Guangxi, 172 (13.18%) had established departments of geriatrics, while 293 (22.45%) boasted departments of rehabilitation medicine. Furthermore, 909 (69.66%) of these institutions offered annual free physical examination services to individuals aged 65 and above. Notably, a total of 362 medical institutions, encompassing both comprehensive hospitals and grassroots hospitals, were recognized as elderly-friendly institutions, accounting for 31.4% of the surveyed sample.The highest demand for talents in medical institutions at all levels included specialized physicians/general practitioners (74.6%), traditional Chinese medicine practitioners (63.1%), rehabilitation therapists (56.1%), and specialized nurses for the elderly (41.7%). A total of 1038 medical institutions conducted popular science activities on elderly health, accounting for 79.5% of the total, focusing mainly on disease prevention (89.21%), nutritional diets (84.68%), rational medication use (79.77%), physical exercise (68.21%), and mental health (60.79%). Only 88 medical institutions provided hospice care services, accounting for 6.7% of the total.Conclusion: Guangxi medical institutions' elderly services are inadequate. Geriatrics and rehab departments are scarce, talent is lacking, and hospice care is underdeveloped. As aging accelerates, the country and society must support elderly care. Governments should introduce talent incentives, and medical institutions should enhance services, foster a positive work environment, and advance Guangxi's elderly health agenda.Keywords: medical institutions, elderly health services, elderly care, hospice care, current status